ANALISIS EFEK KONSEKUENSI PENILAIAN KINERJA PADA MOTIVASI DAN PRODUKTIVITAS KARYAWAN: STUDI PADA TRIBUNNEWS.COM-SOLO - Maimunah, Afifatul; Pradana, Handrio Adhi (Jurnal Fokus Manajemen Bisnis, 2021)
Performance appraisal is acknowledged as one of the most important human resource practices. A performance appraisal system is a critically needed tool for effective human resource management if it is done systematically and effectively. This research examined whether performance appraisal influences employee motivation and employee productivity in Tribunnews.com-Solo. This research was conducted in Solo and the samples of this research were 50 employees of Tribunnews.com-Solo. This research was conducted in the quantitative method by using questionnaires for collecting the data. The data were analyzed with a linear regression test and normality test by using SPSS 25. The results of this research shows that performance appraisal has positive influences on the employee’s motivation and productivity.